‘I am competent so I can be choosy’: choosiness and its implication on graduate employability - Jayasingam, Sharmila; Fujiwara, Yuji; Thurasamy, Ramayah (Taylor & Francis, 2018)
Employability is always used as a measure to gauge the value of graduates. Hence, most past studies attempted to identify competencies that can enhance the level of employability of graduates today. While these past studies found some competencies to be more important than others, the influence of graduate’s attitude, mainly their level of choosiness were not given due consideration. Therefore, this research sets out to determine how choosiness influences the relationship between competencies and employability. We conducted a field experiment with 244 Human Resources executives with considerable experience in employee recruitment and selection. Naturally, highly competent graduates were considered more employable than their less competent counterparts. However, the level of graduate choosiness reduced their employability. Fundamentally, being choosy has a detrimental effect on graduates’ employability.